Organizational culture and management practices at technical vocational education and training colleges - Kaizer Raseane Makole; Bhekabantu Alson Ntshangase; Steven Kayambazinthu Msosa (Institute of Advanced Engineering and Science, 2023)
Building an effective organizational culture of high performance has proven to be elusive amongst strategic and operational managers of selected public technical vocational education and training (TVET) colleges in the Gauteng province in the post-merger period of 2007 to 2010. Poor organizational culture demonstrated by a lack of the Ubuntu principles of humanness and teamwork; management inefficiency and instability undermined the role of public TVET colleges in the Gauteng province, South Africa. The identified knowledge gap is a paucity of information on how the values of Ubuntu are infused into management practices to improve organizational management practices. A mixed methods research approach that adopted multiple case studies, unstructured interviews and survey questionnaires was undertaken to assess an organizational culture and management practices by strategic and operational managers, and lecturers at selected public TVET colleges. Descriptive statistical and thematic analyses were employed to generate, interpret, and analyze the findings from participating managers and lecturers. The findings revealed the need to re-purpose public TVET colleges in South Africa to align with the strategic priorities and goals of the National Development Plan: Vision 2030. Strategic and operational managers should also be capacitated with stakeholder relations building and management skills to create student workplace opportunities with businesses and industries.